2013
DOI: 10.1149/05002.0521ecst
|View full text |Cite
|
Sign up to set email alerts
|

PEMFC Gas Diffusion Media Degradation Determined by Acid-Base Titrations

Abstract: Numerous interlinked processes are responsible for limited durability of polymer electrolyte membrane fuel cells. One of the major phenomena that contribute to accelerated degradation of PEMFCs is loss of hydrophobicity of diffusion media caused by oxidation of carbon in the gas diffusion layer.1 The process is accompanied by formation of oxygen containing surface functional groups. While the vast majority of these groups produce characteristic signals in XPS, DRIFTS, FTIR ATR, etc., frequently an unfavorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This “dissolution” is actually the process of surface‐oxide formation in the carbon‐based GDL in the presence of a liquid electrolyte. It is hypothesized that C−O bonding occurs most commonly on edges of exposed graphene planes, since sp 2 ‐hybridized carbon atoms are more susceptible to oxidation than sp 3 carbon atoms . This oxidation creates two issues.…”
Section: Failure Modes Of Co2 Electrolyzer Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This “dissolution” is actually the process of surface‐oxide formation in the carbon‐based GDL in the presence of a liquid electrolyte. It is hypothesized that C−O bonding occurs most commonly on edges of exposed graphene planes, since sp 2 ‐hybridized carbon atoms are more susceptible to oxidation than sp 3 carbon atoms . This oxidation creates two issues.…”
Section: Failure Modes Of Co2 Electrolyzer Componentsmentioning
confidence: 99%
“…It is hypothesized that CÀOb onding occurs most commonly on edges of exposed graphene planes, since sp 2 -hybridized carbon atoms are more susceptible to oxidation than sp 3 carbon atoms. [40] This oxidation creates two issues. Firstly,t hese surfaces become more hydrophilic due to the CÀOb onds andt he O-containing surface groups.…”
Section: Gdl Failure Modesmentioning
confidence: 99%
“…The GDL becomes hydrated by the water produced during the electrochemical reaction or supplied with hydrogen or oxygen gas. The accumulated water on the GDL can dissolve the GDL carbon material and generate hydroxide, oxides, and other species [74,75].…”
Section: Dissolution Effect On Gdlmentioning
confidence: 99%
“…To overcome the challenges of in situ testing, ex situ accelerated degradation protocols have been developed for the GDL. ,,,− It has been demonstrated that the oxidation of the GDL during long-term fuel cell operation occurs due to the accumulation of liquid water. , Furthermore, it has been suggested that the oxidation of the GDL is enhanced by the presence of hydrogen peroxide (H 2 O 2 ) within the PEM fuel cell. ,, H 2 O 2 formation within the fuel cell occurs when the oxygen reduction reaction follows an alternative pathway as described by Liu et al Based on these oxidation mechanisms, ex situ accelerated degradation protocols for the GDL often involve submerging GDL samples in a solution of H 2 O 2 at elevated temperatures for extended periods of time to mimic the oxidation/corrosion of the GDL during long-term fuel cell operation. ,,,, For instance, Frisk et al degraded GDLs by immersing GDL samples within a solution of 15 wt % hydrogen peroxide (H 2 O 2 ) at 180 °F (82 °C) for extended periods of time (≥72 h). The fuel cell performance of the H 2 O 2 degraded GDLs was then shown to be similar to the performance of fuel cells that had undergone long-term operation .…”
Section: Introductionmentioning
confidence: 99%
“…The fuel cell performance of the H 2 O 2 degraded GDLs was then shown to be similar to the performance of fuel cells that had undergone long-term operation . Chlistunoff et al also studied the degradation of GDLs via immersion in a solution of H 2 O 2 (30 wt % solution at 90 °C for up to 15 h). They demonstrated that the oxidation of the GDL via the ex situ degradation procedure resulted in similar levels of acidic groups on the GDL fiber surfaces compared to GDL materials that had been subjected to long-term fuel cell operation (∼1000 h).…”
Section: Introductionmentioning
confidence: 99%